Adaptive bidding strategy for real-time energy management in multi-energy market enhanced by blockchain. (1st December 2020) - Wang, Longze; Liu, Jinxin; Yuan, Rongfang; Wu, Jing; Zhang, Delong; Zhang, Yan; Li, Meicheng
Highlights: Real-time energy management mode for multi-energy market is proposed. An adaptive learning bidding strategy with reserve price adjustment and dynamic compensation mechanism is developed. The optimized energy trading mode improves economy and renewable energy utilization. Efficient and trustable multi-energy operation is implemented with blockchain. Abstract: Energy trading in the multi-energy market is affected by many uncertainties, especially the fluctuation of renewable energy sources and intermittent demand behavior of customers. The real-time energy management can effectively solve the impact of various uncertainties, ensure the instantaneous balance of energy and improve trading returns. A bidding strategy for multi-energy market is presented, in which reserve price adjustment and dynamic compensation mechanism is innovatively integrated into adaptive learning process. All energy trading participants conduct adaptive learning bidding adjustment based on real-time information in order to obtain higher transaction rate and transaction income. Meanwhile, adding dynamic compensation to the quoted price of fossil energy increases the consumption rate of renewable energy and reduces the emissions of pollutants. Furthermore, blockchain technology can ensure the seamless and effective performance of the presented bidding strategy. In the case study, the results show that our bidding strategy has an obvious advantage in social welfare and allocation efficiency than existing bidding strategies. Moreover, the problem of environmental pollution can be solved to a certain extent through flexible dynamic compensation. Finally, a decentralized application of blockchain is developed to demonstrate how the system could realize real-time energy management and dynamic trading in practice.